Europe between the oceans, 9000 BC to AD 1000 - Cunliffe, Barry W., 1939- (New Haven (Conn.) : Yale university press, 2008)
Space, time and people - The land between the oceans - Food for the garthering - The first farmers - Assimilation in the maritime regions - Europe in her infinite variety - Taking tot the sea, crossing the Peninsula - Emerging Eurozones - The three hundred years that chandes the word - States in collision - The interlude of the empire - THe turn of the tide - Europe rebalances - The longue durée
Keywords: Europe -- Civilization; Europe -- History -- To 476.; Europe -- History -- 476-1492.; Civilization, Western -- History